The state of environmental communication: a survey of PRSA members - Sevick Bortree, Denise (2011)
"Using data collected in a national survey of the professional group Public Relations Society of America, this study authored by Denise Sevick Bortree examines the way that organizations are communicating about the environment. It takes the first step toward understanding how organizations communicate about their environmental policies and practices and how public relations practitioners perceive the environmental transparency of their organizations. Results provide insight into the kinds of topics and channels organizations are using to communicate about environmental topics." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-18888